Farnesoid X receptor agonists attenuate colonic epithelial secretory function and prevent experimental diarrhoea in vivo. Issue 5 (5th August 2013) - Mroz, Magdalena S; Keating, Niamh; Ward, Joseph B; Sarker, Rafiquel; Amu, Silvie; Aviello, Gabriella; Donowitz, Mark; Fallon, Padraic G; Keely, Stephen J
Abstract : Objective: Bile acids are important regulators of intestinal physiology, and the nuclear bile acid receptor, farnesoid X receptor (FXR), is emerging as a promising therapeutic target for several intestinal disorders. Here, we investigated a role for FXR in regulating intestinal fluid and electrolyte transport and the potential for FXR agonists in treating diarrhoeal diseases. Design: Electrogenic ion transport was measured as changes in short-circuit current across voltage-clamped T84 cell monolayers or mouse tissues in Ussing chambers. NHE3 activity was measured as BCECF fluorescence in Caco-2 cells. Protein expression was measured by immunoblotting and cell surface biotinylation. Antidiarrhoeal efficacy of GW4064 was assessed using two in vivo mouse models: the ovalbumin-induced diarrhoea model and cholera toxin (CTX)-induced intestinal fluid accumulation. Results: GW4064 (5 μmol/L; 24 h), a specific FXR agonist, induced nuclear translocation of the receptor in T84 cells and attenuated Cl − secretory responses to both Ca 2+ and cAMP-dependent agonists. GW4064 also prevented agonist-induced inhibition of NHE3 in Caco-2 cells. In mice, intraperitoneal administration of GW4064 (50 mg/mL) also inhibited Ca 2+ and cAMP-dependent secretory responses across ex vivo colonic tissues and prevented ovalbumin-induced diarrhoea and CTX-induced intestinal fluid accumulation in vivo. At the molecular level, FXR activation attenuated apical Cl − currents by inhibiting expression of cystic fibrosis transmembrane conductance regulator channels and inhibited basolateral Na + /K + -ATPase activity without altering expression of the protein. Conclusions: These data reveal a novel antisecretory role for the FXR in colonic epithelial cells and suggest that FXR agonists have excellent potential for development as a new class of antidiarrheal drugs.